ROCK-LANDFORM-SOIL RELATIONSHIP FOR GEOMORPHOPEDOLOGICAL CHARACTERIZATION IN THE REGION OF LAVRA VELHA, OCCIDENTAL CHAPADA DIAMANTINA, BAHIA - Passos, Josue Souza; Ducart, Diego Fernando; Medina, Carlos Martin; de Campos, Alfredo Borges (Revista Brasileira de Geomorfologia, 2020)
The Lavra Velha region is situated on the western edge of the Chapada Diamantina and comprised of a crystalline basement and a metasedimentary cover that corresponds to the Ibitiara Granitoid and the Espinhaço Supergroup, respectively. The Chapada Diamantina is internationally recognized for mineral production and tourism, and because of that it has become a constant target for novel research that aims at characterizing its main geological and physiographic aspects. The present work aims at pointing out geomorphopedological associations of the Lavra Velha region by analyzing the interdependence between rock, landform and soil. To this end, geology, geomorphology and pedology data were obtained from literature, remote sensing data and field expeditions. In the studied area, we recognized metasedimentary and crystalline rocks, on which flat to gently undulating landforms beside crests and cliffs developed. Oxisols occur on flat to gently undulating landforms while Entisols, Inceptisols and rock outcrops appear in the aligned crests, cliffs and undulating hills. Alfisols predominate in undulating hills associated with mafic rocks. Features of the landscape show landforms resembling the Appalachian geomorphological model as first described by William Morris Davis, and they suggest landform evolution by geochemical and mechanical erosion under a strong litho-structural control. The geomorphopedological associations allowed the understanding of the relationship between the major elements of the physical environment from Lavra Velha region and, consequently, a predictive model of the rock-landform-soil distribution that can be useful for geomorphopedological mapping of the western edge of the Chapada Diamantina.